Fear of negative evaluation, subject size of social network, and risk taking - Kim, Kyungil (ProQuest Dissertations & Theses, 2005)
Previous research suggests that members of East Asian cultures show a greater risk preference in financial domains than do members of Western Cultures. Hsee and Weber (1998; 1999) suggest that this difference in risk preference is rooted in subjective size of social network (SSSN) cross cultures. There are some important limitations to this single variable model. I explored the role of SSSN and another candidate variable, fear of negative evaluation (FNE). Previous research suggests that individual differences in social variables (e.g., FNE or interdependence) may explain group differences in cognitive performances. I manipulated both FNE and SSSN in a group of college students and measured their risk preference and used a task that separately assessed the individual relationships between the manipulated factors and the processes of risk taking. The results of Experiment indicate that both SSSN and FNE influence risk preference but in different ways. FNE influences perceived-risk, which in turn affects willingness to pay (WTP) and choice. In contrast, SSSN affects WTP and choice directly without being mediated by perceived risk. These findings clarify the previous work done by Hsee and Weber.